1923 N.H. Laws 138, § 12 - (:unkn) unknown (My University, 1923)
No person shall change, alter, remove, or obliterate the name of the maker, model, manufacturer's number, or other mark of identification on any pistol or revolver. Possession of any such firearms upon which the same shall have been changed, altered, removed, or obliterated, shall be presumptive evidence that such possessor has changed, altered, removed or obliterated the same. Violations of this section shall be punished by a fine of not more than two hundred dollars or by imprisonment for not more
Keywords: DEFACED FIREARMS